Technology-enhanced learning and linguistic diversity : strategies and approaches to teaching students in a 2nd or 3rd language - Mather, Patrick-André (Bingley, U.K. : Emerald Publishing Limited, 2020)
Educators in Europe and the Americas traditionally have little formal training in applied linguistics, and yet they are increasingly faced with a growing multilingual student base. This book responds to the need to make the university community more aware of the unique experience of linguistically diverse students. Drawing on research and hands-on experience from both linguists and non-linguists who deal with students from different language backgrounds in their classroom, this book includes contributions which include linguistic research on 2nd and 3rd language acquisition, as well as case studies of specific challenges in teaching content courses in various disciplines, to offer a roadmap of how educators might facilitate the learning of their bilingual student cohort. Combining issues that have been studied separately within the fields of theoretical linguistics, pedagogy and information and communication technologies (ICT), the author presents a comprehensive overview across the areas of applied linguistics, foreign language teaching methodologies and technological tools to address multilingualism within the university classroom, and ultimately equip educators to meet a critical demand.
Chapter 1.Higher education and the multilingual classroom: how applied linguistics research can help design effective teaching strategies; Patrick-André Mather -- Part I: Third language acquisition and teaching: from theory to practice -- Chapter 2.The Additive Effect of Bilinguals' Metalinguistic Awareness in Additional Language Acquisition; Francesca D'Angelo -- Chapter 3.Learning Spanish and supporting Erasmus students' first language in the interactive classroom; Silvia Chireac -- Chapter 4.Translanguaging Strategies for Teaching Literature in a Multicultural Setting; Maria Teresa Martinez-Garcia, Patricia Arnold -- Chapter 5.On the implementation of language intercomprehension in the American university; Cedric J. Oliva, Alan Gomez -- Chapter 6.Technology-enhanced learning in the L3 German classroom; Sven-Ole Andersen -- Chapter 7.The intersection of language, culture and technology: Perceptions of L3 learning by L2 speakers of English; Chesla Ann Lenkaitis, Shannon M. Hilliker, Luis Y. Castañeda -- Chapter 8.Students' attitudes towards critical telecollaboration: A case study in an L2/L3 French classroom; Vincent Chanethom -- Part II: Teaching college and university-level content courses in an additional language -- Chapter 9.Technology-enhanced lesson plans for multilingual students; Anna Moni -- Chapter 10.Teacher-training programs in Physical Education for African-American and Hispanic students; Langston Clark, Carlos M. Cervantes -- Chapter 11.The Cumulative Curriculum Model for Content and Language Development in the Multilingual Classroom; Robb McCollum -- Chapter 12.Second and third language acquisition and the multilingual classroom: new insights for higher education; Patrick-André Mather.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Second language acquisition; Second language acquisition -- Study and teaching; Educational technology; Education, Bilingual Education; Bilingualism & multilingualism